Overview of Niphargidae (Crustacea: Amphipoda) in Belgium: distribution, taxonomic notes and conservation issues - Fišer, Cene; Zagmajster, Maja; Dethier, Michel (Zootaxa, 2018)
Niphargidae is among the largest families of freshwater subterranean amphipods in the world, and one of the most important macroinvertebrate groups in European groundwaters. The knowledge of their species diversity on a country level is often incomplete due to demanding taxonomy. In this paper we critically evaluated species diversity of the family in Belgium, using published records and samples from our own field work. Morphology-based identifications confirmed the presence of genera Microniphargus and Niphargus, represented with one and eight species, respectively. Most of the species found in Belgium belonged to complexes of cryptic species, which are still awaiting their taxonomic epilogue. Four species belong to phylogenetic lineages distributed also across British Isles, whereas three species belong to lineages distributed in the west-continental Europe. Identity of one species was doubtful, and two populations, partially illustrated herein, showed distinct morphology and might belong to a new species. All together, Niphargidae were found at 172 localities, with 80% of sites harboring one species only. At 12 localities three to six species co-occurred. When mapped onto 10x10 km grid, up to seven different species were recorded per quadrate. Species richest quadrates were situated in the southeastern part of the country. Paucity of records from the northern part of the country imply lack of research, rather than absence of Niphargidae. Conservation status of Belgian Niphargidae has not been evaluated so far; assessment of this status would require further sampling and detailed taxonomic work.